Influence of Geology and Relief on the Society Evolution - Nazaruk , M. M.; Maksymenko , N. V. (Man and Environment. Issues of Neoecology, 2021)
The main aim of this article is to consider the way geological and geomorphological processes on the planet Earth have influenced intellect, language, mastering of tools, social studies and cooperative behaviour, which helped society develop agriculture, live in the cities and build civilization. The formation of society has covered a long and difficult way on the planet Earth.Today society is regarded as a human being, stipulated by action and communication, a system of social living together, during which a person and his spirituality is formed as a result of a society’s transformation into some kind of its social existence. Man is in the centre of a society, which cannot exist without him. Society is a system of social living together. It originated from nature’s evolution, having acquired its characteristic features from the very beginning. Despite a wide interpretation of nature and society cooperation, we agree that the fundamental correlation of biological and social in our science are considered very simply. The biological is identified as the animal, the geological - as lifeless nature, but social - as human. The formation of ancient civilizations at the junctions of lithospheric plates confirms that the quintessence of inanimate (geological processes) development is precisely the surge of the living - human society. Particularly high concentration of the developed ancient civilizations is found on the Mediterranean-Himalayan-Indonesian seismic belt, where the network of latospheric plates joins. Later, in the process of society's evolution, the influence of the "inanimate" on the quantitative and qualitative characteristics of the "living" is increasingly manifested. It has been proved that the relief as a result of geological factors "work",  acts as the essential lever in it. The isolated development of ancient societies is singled out, caused, first of all, by the environment of mountain systems.Conclusion. We notice that the idea of socio-natural world’s character, the coevolution principle as productive means of cognition and solution to the problem of the society and the Earth planet cooperation acquires an important methodological and world outlook meaning